Multigenerational exposure of microplastics on the microbiota of E. affinis (copepod): a comparative study between biodegradable and nonbiodegradable microplastics - Thery, Jérémy; Li, Luen-Luen; Das, Shagnika; Dufour, Dylan; Benali, Samira; Raquez, Jean-Marie; Souissi, Sami; Monchy, Sébastien (Frontiers in Ecology and Evolution, 2023)
The accumulation of plastic debris around the world, especially in marine environments, has been well documented during the past decades. Recent studies have found that inorganic surfaces of microplastics (MPs) can be used by microorganisms as living substrates and form an ecosystem named “plastisphere.” Some microorganisms present in MPs are capable of producing polymer-degrading enzymes. In addition, MPs can also serve as vectors and carry microorganisms (including potential pathogens) into higher trophic levels through their ingestion by animals. In this study, impacts on copepod microbiota during chronic exposure to MPs were investigated by exposing copepods to a classic single-use polymer (low-density polyethylene (LDPE)) and a biodegradable polymer (polybutylene adipate terephthalate (PBAT)). Copepods were exposed to “virgin” and “weathered” MPs during four generations at an environmentally relevant concentration of 300 µg/L, followed by one “detoxification” generation without MP exposition. Impacts of MP exposure on copepod microbiota were investigated using 16S rRNA gene high-throughput sequencing. The result of nonmetric multidimensional scaling (NMDS) analysis showed that copepods (with or without MP exposure) carried distinguishable microbiota as compared with the microbiota of water and microalgae used for maintaining copepods. According to the results of permutational analysis of variance (PERMANOVA), the microbiota of MP-exposed (both PBAT and LDPE) copepods was significantly different from the microbiota of unexposed copepods during generations one to four. After “detoxification,” however, no significant difference in microbiota composition was observed among all generation five copepods. Altogether, impacts on copepod microbiota of MP exposure for multiple generations were observed, despite plastic origin (biodegradable or not) and aging conditions. Furthermore, copepod microbiota seemed to return to their original structure as soon as the MP exposure stopped.